In search of a dialogue: Digital di-plomacy of Sweden - A. N. Marchukov (Вестник Московского Университета. Серия XXV: Международные отношения и мировая политика, 2022)
Digital diplomacy opens up new opportunities for both developed and devel-oping states to promote their international image, clarify their position on current issues, and realize long-term foreign policy aspirations, but it also brings com-pletely new challenges. The chief one among them is establishing a continuous constructive dialogue with the target audience in the virtual space. Facilitation for this dialogue is one of the key priorities of the digital diplomacy of Sweden. The author examines the activities of the key actors of Sweden’s digital diplomacy (the Ministry of Foreign Aﬀ airs of Sweden, the Swedish Institute, the Swedish Tourist Association (Svenska Turistföreningen), ‘Visit Sweden’) and identiﬁ es their key features. Particularly, the author emphasizes the government’s readiness to implement innovative and creative methods to promote its media projects. The latter include such projects as ‘The Second House of Sweden’, ‘Curators of Sweden’, and ‘Swedish Number’, which were aimed at improving the quality of communication with the foreign audience. In doing so, the responsible minis-tries and agencies placed a heavy emphasis on promoting a dialogue via social networks between the Swedish oﬃ  cials and representatives of the civil society on the one hand and foreign users on the other. The leading actors of Sweden’s digital diplomacy actively engaged the foreign audience in discussions on the most important issues on the foreign policy agenda of Sweden. This was most clearly demonstrated in media campaigns designed to eliminate discrimination against women and gender-based violence. The author concludes that Sweden has achieved a certain degree of success in establishing a dialogue with the foreign audience, yet this dialogue is not comprehensive enough and still depends on the initiative of individual politicians and diplomats.